‘Some strange monster of the isle’: l’hybride dans The Tempest - Pascale Drouet (Revue LISA)
This article focuses on the hybrid and how it is put into perspective on Prospero’s island. First Caliban is examined as both a biological and cultural hybrid pervading the imaginary field and as the touchstone of the related dialectics of rejection and appropriation. Then, from a metaphorical point of view, Prospero’s island is regarded as a cabinet of curiosities in which hybrid creatures—of which Caliban is one—fill the castaways with either wonder or horror; Prospero’s project and that of creators of cabinets as “encyclopaedias of the visible world” (Evans’ phrase) may hence be paralleled. Finally, the hybrid as revealing hubris, Prospero’s “Promethean attitude” (Hadot’s term) and the irreducible quality of the hybrid are examined.